IMPLEMENTASI BRANDING “KOTA REMPAH” UNTUK MENINGKATKAN KUNJUNGAN WISATAWAN DI KOTA TERNATE - Delayla Qadriyah, Siti; Sudiarta, I Nyoman; Suwena, I Ketut (Jurnal IPTA (Industri Perjalanan Wisata), 2024)
“Kota Rempah” branding is the newest characteristic of Ternate City in North Maluku to promote superior tourism potential which has been the main tourism attraction in Ternate City with the hope of being able to increase the level of tourist visits, move the wheels of the economy, improve the region's image & competitiveness on the national and international stage. The purpose of this research was to find out how the promotional mix for the “Kota Rempah” branding was implemented by the Ternate City Tourism Department to increase tourist visits to Ternate City as well as the obstacles faced by the Tourism Department in carrying out the Spice City branding promotion. This research is a qualitative descriptive research with data collection techniques using observation, interviews, documentation. The technique for determining informants in this research used a purposive sampling technique with three people as informants. The results of this research show that the promotional mix used by the Ternate City Tourism Office is advertising through print and electronic media, sales promotions in the form of discounts on local products, individual sales through the Tourist Information Center, and public relations through collaboration with the tourism industry, Generasi Pesona Indonesia, Ternate geopark youth forum and other state-owned companies. In implementing promotions, there are also obstacles faced such as the lack of a promotional budget and global competition.